Social science research priorities for national development : (proceedings of a national seminar) - Nigerian institute of social and economic research Ibadan (Ibadan : NISER, 1981)
This is a report of a National seminar that was organized by Nigerian Institute of Social and Economic Research (NISER) The seminar was motivated by a need to identify research priorities for NISER's research work programme.
(Proceedings and conclusions of a national seminar) June 1981
ahz 04/04/2019
Loans
Keywords: Social sciences; National development; Nigeria